Women, intuition, and management—the Yin and Yang of nonconscious thought - Isenman, Lois; Sinclair, Marta (Frontiers in Psychology, 2025)
This article explores the claim that men’s and women’s intuition tend to differ in some way, and that women’s intuition can make a distinctive contribution to leadership and management. In response to the dynamic and unpredictable nature of the current business environment, intuition has received increased attention from the business community. Likewise, it has become an intense area of academic research, along with the unconscious knowledge and integration on which it largely depends. Although both women and men process information partially below awareness, there are likely some distinctions. Research shows that in many situations men tend to simplify information and focus primarily on its most salient aspects. In contrast, women tend to utilize information more completely, with greater sensitivity to the inter-relationships between different pieces, to context and to anomalies. We propose that there is an affinity between intuition and the way that women prefer to deal with information, and that much of their higher-level information processing and elaboration may occur below awareness. Recent work also indicates that women are more receptive to emotional and other body-based signals, which can help surface unconscious knowledge. Their greater focus on completeness and interconnections together with their emotional and bodily sensitivity tends to make them more open to additional information at both the unconscious and conscious level. Therefore, women’s intuition, although it can take time to germinate, has the potential to foster decision making, problem solving and human resources management that are more multifaceted and holistic. Male intuition, in contrast, seems to support expert behavior and efficiency. We suggest that taking advantage of women’s intuition in the workplace would require a twofold adjustment: women would need to gain confidence in their intuition and organizations would need to recognize its potential power.